Pelatihan Peningkatan Kemampuan Berbicara Bahasa Inggris Melalui Model Synectics pada Siswa SMAN 6 Betara Tanjung Jabung Barat - Abrar, Mukhlash; Mayasari, Mayasari; Failasofah, Failasofah; Sartika, Delita; Handayani, Reli (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
This study examines the effectiveness of training aimed at enhancing English speaking skills among students at SMAN 6 Betara, Tanjung Jabung Barat, through the Synectics model. The Synectics approach, known for fostering creativity and critical thinking, encourages students to explore abstract concepts and express their thoughts through metaphors and analogies. This method not only promotes language proficiency but also enhances students' confidence and engagement in the learning process. The training program involved interactive activities, structured group discussions, and creative exercises, which allowed students to practice speaking in a supportive environment. Pre- and post-training assessments indicated significant improvements in vocabulary usage, pronunciation, and overall speaking fluency. The findings suggest that the implementation of the Synectics model in language education can lead to more dynamic and effective learning experiences, ultimately contributing to better communication skills among high school students. The study highlights the importance of innovative teaching strategies in language education and recommends further integration of creative methodologies to improve speaking abilities in non-native English contexts. Future research could explore the long-term effects of such training and its impact on students' overall academic performance.